Positive Predictive Value of MOG-IgG for Clinically Defined MOG-AD Within a Real-World Cohort - Manzano, Giovanna S.; Salky, Rebecca; Mateen, Farrah J.; Klawiter, Eric C.; Chitnis, Tanuja; Levy, Michael; Matiello, Marcelo (Frontiers in Neurology, 2022)
Myelin oligodendrocyte glycoprotein antibody associated disease (MOG-AD) is a CNS demyelinating disease, typically presenting with optic neuritis, transverse myelitis, and/or ADEM-like syndromes. The positive predictive value (PPV) of MOG-IgG testing by live cell-based assay was reported to be 72% in a study performed at the Mayo Clinic using a cut-off of 1:20. PPV may vary depending upon the tested population, thus supporting further investigation of MOG-IgG testing at other centers. In this real-world institutional cohort study, we determined the PPV of serum MOG-IgG for clinically defined MOG-AD in our patient population. The Massachusetts General Brigham Research Patient Data Registry database was queried for patients with positive serum MOG-IgG detection, at least once, between January 1, 2017 and March 25, 2021. All were tested via the MOG-IgG1 fluorescence-activated cell sorting assay (Mayo Laboratories, Rochester, MN). MOG-IgG positive cases were reviewed for fulfillment of typical MOG-AD clinical features, determined by treating neurologists and study authors. Of 1,877 patients tested, 78 (4.2%) patients tested positive for MOG-IgG with titer ≥1:20, and of these, 67 had validated MOG-AD yielding a PPV of 85.9%. Using a ≥1:40 titer cutoff, 65 (3.5%) tested positive and PPV was 93.8%. Three MOG positive cases had a prototypical multiple sclerosis diagnosis (RRMS n = 2, titers 1:20 and 1:40; PPMS n = 1; 1:100). The treating diagnosis for one RRMS patient with a 1:40 titer was subsequently modified to MOG-AD by treating neurologists. Validated diagnoses of the remaining positive patients without MOG-AD included: migraine (n = 2, titers 1:20, 1:100), inclusion body myositis (n = 1, titer 1:100), autoimmune encephalitis (n = 2, titers 1:20, 1:20), hypoxic ischemic brain injury (n = 1, titer 1:20), IgG4-related disease (n = 1, titer 1:20), and idiopathic hypertrophic pachymeningitis (n = 1, titer 1:20). In our cohort, the PPV for MOG-IgG improved utilizing a titer cut-off of ≥1:40. The presence of positive cases with and without demyelinating features, emphasizes a need for testing in the appropriate clinical context, analysis of titer value and clinical interpretation.